Implementasi Virtual Private Network Pada Jaringan Multi Protocol Label Switching Traffic Engineering - ade Nurhayati; Risnu Pradana Holiyastuta; Ade Rahmat Iskandar (Journal of Informatics and Communication Technology (JICT), 2020)
Along with the development of telecommunications technology, we need a network that provides traffic services to send data to distant places quickly but does not forget about security, some solutions are the Multi Protocol Label Switching method, Virtual Private Network, and Traffic Engineering. MPLS VPN TE is a combination of several methods that can be used for this problem. In this research, simulation is carried out using GNS3 software and the results of the analysis are carried out using a Wireshark software. This scenario uses the measurement load using FTP and HTTP. The measurement parameters of QoS are transfer time, throughput, delay, and packet loss ratio. The measurement results show that QoS value for transfer time of 25 MB file is 16.94s, and transfer time for HTTP is 4.2 s. The Throughput of 25 MB file is 1.606MB/s, and throughput for HTTP is 5.6 MB/s. The Delay of 25MB file is 1.22 ms, and delay HTTP is 105.37 ms